Analisis Life Cycle Cost dan Keberlanjutan Material Keramik Granit (Studi Kasus Toko Bangunan Mitra Megah Bangunan, Tulungagung) - Fajar Zidane Rahmanian; Sony Susanto (Institut Teknologi Garut, 2026)
This study aims to analyze the selection of sustainable granite ceramic materials based on Life Cycle Cost (LCC) and sustainability aspects at the Mitra Megah Building Materials Store, Sumbergempol, Tulungagung. The research method includes collecting material price data from online marketplaces (Tokopedia) and field verification, followed by LCC calculations and an assessment of the Material Sustainability Score (SKM), which covers environmental, social, and economic aspects. The results show that vinyl/PVC ceramics have the lowest initial cost but result in the highest life cycle cost (IDR 437,830/m²) due to their short service life. In contrast, locally produced granite, although having a higher initial cost, yields the lowest life cycle cost (IDR 324,091/m²). In terms of sustainability, recycled-based materials such as local terrazzo achieve the highest score (SKM = 86) because they utilize marble waste and support the local economy, while imported granite obtains the lowest score (SKM = 68) due to the carbon footprint associated with transportation. These findings highlight the importance of selecting local and recycled materials in sustainable construction. Therefore, this study recommends the use of local granite and local terrazzo as the main sustainable material alternatives that balance long-term cost efficiency and environmental sustainability.